2022
DOI: 10.3390/jcm11226770
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Failure of Ultrasound Cyclo Plasty for Primary Open-Angle Glaucoma

Abstract: Aims: To evaluate the outcomes of ultrasound cyclo plasty (UCP) for primary open-angle glaucoma (POAG) and identify the predictors of failure. Methods: This retrospective cohort study included patients with POAG who underwent UCP at King Abdul Aziz University Hospital, Riyadh, Saudi Arabia, between 2016 and 2021. The main outcome measures were the intraocular pressure (IOP), the number of antiglaucoma medications, and the presence of vision-threatening complications. The surgical outcome of each eye was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Starting from the 1980s, ultrasound began to be used for the treatment of glaucoma [24] . High-intensity focused ultrasound was applied non-invasively to the ciliary processes that produce aqueous humor, for precise, controlled, and gentle thermal coagulation, melting the epithelial cell layer of the ciliary body while preserving the blood-aqueous humor barrier, reducing aqueous humor production, opening the uveoscleral pathway, increasing aqueous humor outflow, and achieving a dual reduction in IOP [12,[25][26][27] . The precise focusing causes no damage to non-treatment areas, does not cause eye shrinkage, is not affected by pigment absorption, and the degree of pressure reduction is controllable, without causing low eye pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the 1980s, ultrasound began to be used for the treatment of glaucoma [24] . High-intensity focused ultrasound was applied non-invasively to the ciliary processes that produce aqueous humor, for precise, controlled, and gentle thermal coagulation, melting the epithelial cell layer of the ciliary body while preserving the blood-aqueous humor barrier, reducing aqueous humor production, opening the uveoscleral pathway, increasing aqueous humor outflow, and achieving a dual reduction in IOP [12,[25][26][27] . The precise focusing causes no damage to non-treatment areas, does not cause eye shrinkage, is not affected by pigment absorption, and the degree of pressure reduction is controllable, without causing low eye pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It does not require incisions, has a fast recovery, and allows for quick subsequent anti-VEGF or PRP treatment. The procedure is simple and the treatment time is short, only a few minutes, which improves the efficiency of clinical treatment [13][14][15]25,28] . The results of this study showed that the IOP of both groups of patients with NVG significantly decreased at each postoperative time point compared to preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported encouraging short-term results regarding the safety and efficacy of UCP. [8][9][10][11][12][13][14] However, little is known about its outcomes in PACG. Therefore, our study aimed to report the intermediate-term outcomes of UCP in eyes with PACG.…”
mentioning
confidence: 99%
“…Both the miniaturized transducers and the circular-shaped probe matching the 3-dimensional anatomy of the ciliary body allow correct focusing of ultrasound beams on the target tissue through optically opaque ocular media with controlled energy absorption. Several studies have reported encouraging short-term results regarding the safety and efficacy of UCP 8–14. However, little is known about its outcomes in PACG.…”
mentioning
confidence: 99%